Histopathological biomarkers in juvenile silver catfish (Rhamdia quelen) exposed to a sublethal lead concentration - Muñoz, Lautaro (2015)
The aim of this study was to determine the 96-h lethal concentration (96-h LC50) of lead (Pb) in silver catfish, Rhamdia quelen, and to determine histopathological biomarkers in fish exposed for 96-h to a sublethal concentration at 25% of the LC50. The 96-h LC50 was 108 mg l−1. In gills, the length and thickness of lamella and thickness of the filament epithelium were significantly higher in fish exposed to Pb for 48-h than in control fish whereas the interlamellar distance decreased. In the liver, the area occupied by lipid droplets and size of hepatocytes showed significantly higher values after 24-h of exposure. The percentage of abnormal renal tubules was higher in fish exposed to Pb, exhibiting a time-dependent increase. These variations in histopathological biomarkers permit the definition of the overall response of R. quelen to Pb and the potential usefulness in the monitoring of Pb contamination.